Teachers' Perceptions of the Work Climate: Implications for Teacher Performance and Professionalism in Vocational High School - Salsabillah, May Piola; Santoso, Yulianto; Al Kadri, Hanif; Hayati, Nikmah (Journal of Educational Management Research, 2025)
In the context of vocational education, the school work climate significantly influences teacher performance, motivation, and commitment. While teachers are expected to exhibit high professionalism, many vocational high schools still lack a conducive environment that fosters collaboration, support, and participation. This study explores how teachers perceive the work climate in state vocational high schools. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and documentation. The findings reveal that teachers perceive institutional support as a key element of a positive work climate, reflected through leadership responsiveness, mentoring systems, and inclusive academic planning. Ideal support is shown to be multidimensional, structural, relational, and participatory, promoting teacher engagement, psychological comfort, and a sense of belonging. These findings contribute to a deeper understanding of the psychosocial dimensions that shape the school environment and provide empirical insights for policy interventions aimed at improving the quality of teacher professionalism and educational outcomes in vocational schools.